ARBITRATION IN LABOR LAW: Limits and applicability before the effectiveness of the principle of protection (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
In this moment of dogmatic effervescence about the proposal of labor reform, moral, economic, distrust of public opportunities and their reflexes in the labor market, these questions only haunt and bring uncertainties as benefits. The present study must be applied to the arbitration, its current panorama, is one of the paradigms of the individual use of the work, in the same way, to the contrary, of the same. Scope, ONLY For Some Few Employees, Exhibiting The Challenges That Arbitrage Might Have Ample Utilization Without Labor Law By Proposing Solutions And New View Of Arbitrage Not That It Says Respect To Direct Labor Individual And New View Of Arbitrage Does Not respect to the individual's individual work.KEYWORDS: Labor Reform. Contract of work. Autonomy. Labor arbitration.